The Economic and Social Capital Factors in the Victory of Independent Candidate Pairs in the 2020 Regional Head and Deputy Regional Head Elections of Metro City - Muhammad Yoridho Ambiya (Eduvest - Journal of Universal Studies, 2024)
Based on KPU Regulation Number 1 of 2020 which regulates the nomination of regional heads and deputy regional heads in the 2020 simultaneous regional elections, there are changes to the nomination requirements from the individual path. Data on the results of the 2020 regional elections show that there were six individual candidate pairs who won the elections, one of which was in Metro City, Lampung province. The victory of individual candidate pairs in the Metro City regional elections can be said to break the dominance of candidate pairs from political parties who always win elections. This research examines the victory of candidate pairs Wahdi and Qomaru from the perspective of political, economic and social capital. The theory of capital refers to Pierre Bourdieu (1992), and is supported by the theory of political capital from John A. Booth and Patricia Bayer Richard (1998). The research method is qualitative with primary data collection through in-depth interviews. The research findings show that social capital (grassroots network), and economic capital (capital control) became the main factors of Wahdi and Qomaru's victory, which succeeded in defeating a pair of candidates from political parties, making it the first time Metro City was led by a mayor and deputy mayor not from a political party.